Why do people purchase antibiotics over-the-counter? A qualitative study with patients, clinicians and dispensers in central, eastern and western Nepal. Issue 5 (11th May 2021) - Adhikari, Bipin; Pokharel, Sunil; Raut, Shristi; Adhikari, Janak; Thapa, Suman; Paudel, Kumar; G C, Narayan; Neupane, Sandesh; Neupane, Sanjeev Raj; Yadav, Rakesh; Shrestha, Sirapa; Rijal, Komal Raj; et al.
Abstract : Introduction: Over-the-counter (OTC) use of antibiotics contributes to the burgeoning rise in antimicrobial resistance (AMR). Drawing on qualitative research methods, this article explores the characteristics of OTC sales of antibiotic in Nepal, its drivers and implications for policy. Methods: Data were collected in and around three tertiary hospitals in eastern, western and central Nepal. Using pre-defined guides, a mix of semi-structured interviews and focus group discussions were conducted with dispensers at drug stores, patients attending a hospital and clinicians. Interviews were audio-recorded, translated and transcribed into English and coded using a combination of an inductive and deductive approach. Results: Drug shops were the primary location where patients engaged with health services. Interactions were brief and transactional: symptoms were described or explicit requests for specific medicine made, and money was exchanged. There were economic incentives for clients and drug stores: patients were able to save money by bypassing the formal healthcare services. Clinicians described antibiotics as easily available OTC at drug shops. Dispensing included the empirical use of broad-spectrum antibiotics, often combining multiple antibiotics, without laboratory diagnostic and drug susceptibility testing. Inappropriately short regimens (2–3 days) were also offered without follow-up. Respondents viewed OTC antibiotic as a convenient alternative to formal healthcare, the access to which was influenced by distance, time and money. Respondents also described the complexities of navigating various departments in hospitals and little confidence in the quality of formal healthcare. Clinicians and a few dispensers expressed concerns about AMR and referred to evadable policies around antibiotics use and poor enforcement of regulation. Conclusions: The findings point to the need for clear policy guidance and rigorous implementation of prescription-only antibiotics.